Development of Flexibility Training Model Through Games in Takraw Extracurricular Football - Hasriyanti Hasriyanti; Iyakrus Iyakrus; Destriani Destriani (Journal Physical Education, Health and Recreation, 2021)
This study aims to produce a model of flexibility training through games in the extracurricular sepak takraw MTS Islamic Boarding School Masdarul Ulum Ogan Ilir. The type of research used is researh and development (r&d),/ development. Small – scale trials in this study were students of class VII MTS Islamic boarding school Masdarul Ulum Ogan Ilir. totaling 10 people. Develompent research refers to the develompent step which is modifled into two stages (1) pre-develompent (2) develompent. Large – scale trlals in this. Large –scala trials in the rescarch in this study were studens of class VIII Mts Islamic Boarding School Masdarul Ulum Ogan Ilir, tataling 30 people. The data collection instrument used an expert validations sheet, a rating scala. The data analysis technique used a reference research for pretest and posttest for small groups and large groups.research product that producec a model of flexibility training through games in sepak takraw extracuarricular.